2022
DOI: 10.3390/toxins14010036
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Efficacy of Botulinum Toxin A for Neuropathic Pain

Abstract: We performed a systematic review and meta-analysis of randomised controlled trials (RCTs) conducted from January 2005 to June 2021 to update the evidence of Botulinum toxin A (BoNT-A) in neuropathic pain (NP) in addition to quality of life (QOL), mental health, and sleep outcomes. We conducted a Cochrane Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria analysis of RCTs from the following data sources: EMBASE, CINAHL, WHO International Clinical Trial Registry Platform, Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Botulinum toxin type A has been used for years in the fields of neurology, rehabilitation and physical medicine and has proven to be an innocuous and effective therapy. 13 , 22 It seems that BoNT-A might also be effective for the comprehensive management of neuropathic pain, especially for diabetic polyneuropathy. 23 BoNT-A can accelerate nerve regeneration and improve functional recovery after injury to peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum toxin type A has been used for years in the fields of neurology, rehabilitation and physical medicine and has proven to be an innocuous and effective therapy. 13 , 22 It seems that BoNT-A might also be effective for the comprehensive management of neuropathic pain, especially for diabetic polyneuropathy. 23 BoNT-A can accelerate nerve regeneration and improve functional recovery after injury to peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“… 12 With regard to its effects on pain, some possible mechanisms of BoNT-A include retrograde axonal transport of toxins, inhibition of neuropeptides, such as substance P and calcitonin gene-related protein (CGRP), glutamate and deactivation of Na channels. 13 …”
Section: Introductionmentioning
confidence: 99%
“…In the first round of injections, we treated only the ulnar territory, while in the following rounds, we decided to apply a more widespread approach with an improvement of the efficacy on the pain and disability as well as a longer duration of the benefit; in fact, low doses of BoNT/A are insufficient for the spreading into the central nervous system [36,38]. Regarding the efficacy of BoNT/A in neuropathic pain, a recent meta-analysis of randomized controlled studies reported greater efficacy of BoNT/A in reducing pain than placebo [39]. In the context of CRPS, a meta-analysis of placebo responses in long-standing CRPS patients reported no evidence of placebo response [40], but there were no studies regarding therapy with BoNT/A.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive local BoNT/A1 injection seems to be a safe and effective therapy in long-term management for chronic neuropathic pain (Ri et al 2021 ). The most recent systematic review and meta-analysis of randomized controlled studies added evidence that BoNT-A1 is safe for treating neuropathic pain, without notable side effects, and it is durable over an extended period (Datta Gupta et al 2022 ).…”
Section: Novel Therapeutic Applications Of Botulinum Neurotoxinsmentioning
confidence: 99%